Sequential use of mushroom body neuron subsets during drosophila odor memory processing. - Krashes, M; Keene, A; Leung, B; Armstrong, J; Waddell, S (2007)
Drosophila mushroom bodies (MB) are bilaterally symmetric multilobed brain structures required for olfactory memory. Previous studies suggested that neurotransmission from MB neurons is only required for memory retrieval. Our unexpected observation that Dorsal Paired Medial (DPM) neurons, which project only to MB neurons, are required during memory storage but not during acquisition or retrieval, led us to revisit the role of MB neurons in memory processing. We show that neurotransmission from the alpha'beta' subset of MB neurons is required to acquire and stabilize aversive and appetitive odor memory, but is dispensable during memory retrieval. In contrast, neurotransmission from MB alphabeta neurons is only required for memory retrieval. These data suggest a dynamic requirement for the different subsets of MB neurons in memory and are consistent with the notion that recurrent activity in an MB alpha'beta' neuron-DPM neuron loop is required to stabilize memories formed in the MB alphabeta neurons.